PENGARUH STRATEGI PEMBELAJARAN METACOGNITIVE SCAFFOLDING TERHADAP HASIL BELAJAR MENULIS TEKS ULASAN - Andi Palompai. A; Sakaria Sakaria; Asis Nojeng (Universitas Negeri Makassar, 2025)
This study aims to describe the results of writing review texts by eighth-grade students at SMPN 27 Makassar before and after using the metacognitive scaffolding learning strategy and to prove the effect of using the metacognitive scaffolding learning strategy on the results of writing review texts by eighth-grade students at SMPN 27 Makassar. This study used a quantitative approach with a pre-experimental research design (One Group Pretest-Posttest Design). Data were collected through review text writing tests before (pretest) and after (posttest) the use of the metacognitive scaffolding learning strategy. The data analysis used in this study was descriptive statistical analysis and inferential statistical analysis. The results showed that there was a significant difference between students' review writing learning outcomes before and after using the metacognitive scaffolding learning strategy. Data analysis showed that the pretest mean score was 59.69, while the posttest mean score was 85.38. The Wilcoxon test results showed that the significance value was < 0.001, which means it was less than 0.05. Thus, it can be concluded that there is an effect of using the metacognitive scaffolding learning strategy on the learning outcomes of writing review texts by students in class VIII of SMPN 27 Makassar.